(untitled) (Research, Society and Development, 2023)
Patients with HIV infection may have different causes and manifestations for kidney disease, from subclinical proteinuria to acute renal failure. It can be caused both by the direct effect of HIV on the kidneys and by the nephrotoxic effect of antiretroviral medications. The objective of this study is to evaluate renal dysfunction and relate it to the glomerular filtration rate (GFR) of patients followed up in a reference outpatient clinic for patients living with HIV/AIDS (PLWHA). This is a cross-sectional, retrospective, non-interventionist study, carried out by reviewing the medical records of patients treated from 2017 to 2020, at the HIV outpatient clinic of a reference quaternary hospital in Fortaleza, Ceará, Brazil. The results evaluated 77 patients, aged between 32 and 77 years, 63.6% male and 35.1% female, in addition to 1.3% transsexual (N=1). 113 measurements of renal function markers were analyzed and correlated with the calculation of glomerular filtration rate (GFR) through age and the creatinine value by the MDRD GFR equation, with 32.7% (N=37) with normal GFR. The mean MDRD was 81.7 mL/min/1.73m2, mean protein/creatinuria ratio 0.16 (N=69) and mean beta2microglobulin of 2.4 ng/ml, with 60.5% of altered dosages (> two). Most frequent comorbidities: Diabetes mellitus (27.3%), SAH (22%), Dyslipidemia (28.6%) and kidney disease 14.3%). The preferred regimen, tenofovir, lamivudine and dolutegravir, was used by 33% of patients; 5.4% followed a simplified scheme with lamivudine and dolutegravir. Detectable viral load found in 9.8% of records. We conclude that patients have a high prevalence of kidney disease in PLWHA that correlate with the presence of comorbidities and tubular changes.